Influence of Macro Environment on the Performance of Business Process Outsourcing Companies in Kenya - Chege, Purity N. (University of Embu, 2021)
Business Process Outsourcing is one of the six priority sectors in the economic pillar of the Kenya Vision 2030. The vision envisages that the country becomes the top business process outsourcing destination in Africa. However, this has not been achieved since some other countries like South Africa, Ghana, Morocco, and Egypt have been more preferred destinations than Kenya. Statistics have also shown that the global business process outsourcing destination position for Kenya has deteriorated. It is in this regard that this study sought to establish the influence of macro environment on the performance of the business process outsourcing companies in Kenya. The study was underpinned by four theories, namely, Open systems, Porters Diamond, Contingency and Macro Environment model. Pragmatic paradigm was used to support the mixed research approach used in the study. The target population consisted of all 118 registered business process outsourcing companies in Kenya. Primary data was collected using a questionnaire with a Likert-type interval using a five-point scale. Additionally, secondary data from 2014 to 2017 on performance, namely, the number of services and return on assets was collected. To improve the reliability and validity of data, pretesting of the research instrument was carried out on 12 companies. Cronbach's reliability coefficients ranged from 0.740 to 0.891 which was more than 0.7 and thus the research instrument was found to be reliable and valid for the study. Tests on assumptions of the regression models namely, linearity, multicollinearity, autocorrelation and heteroscedasticity were all met. Descriptive statistics showed the features and patterns of the data. Analysis of variance showed that there was a significant relationship between all the independent variables with the dependent variable. The regression analysis was carried out through testing of five null hypotheses which were all rejected since there was a statistically significant influence of political, economic, technological, and legal environments on the performance of business process outsourcing companies in Kenya. Further, there was a moderating influence of firm strategy on the performance of the business process outsourcing companies in Kenya. The study recommends that the companies adopt new technology, come up with innovations of doing business, expand their offshore business by positioning themselves internationally and diversify their services. Regarding policy, the study recommends that the cybercrimes legislation be reviewed and amended continuously to address the emerging cybercrimes to ensure the security of customer data in possession of the business process outsourcing companies. The study recommends that other studies be replicated in other sectors and countries to establish whether the results would be similar. In addition, studies may be carried out on the combined influence of both micro and macro environments while other variables be considered as moderators between macro environment and performance while the firm strategy may be considered as one of the independent variables to establish its influence on performance. The study has provided contribution to the Contingency Theory by establishing a positive influence of external environment on performance and particularly the economic and technological environments.